PENGARUH KOMPOSISI PENGISI SERTA TEKANAN HOT PRESS TERHADAP KEKUATAN TARIK KOMPOSIT POLIESTER BERPENGISI PARTIKEL ZINC OXIDE (ZnO) - Hamzah Arifin Sinambela; Maulida (Talenta Publisher (Universitas Sumatera Utara), 2018)
The aim of this research was to determine the effects of filler loading and pressure of hot press on tensile strength of zinc oxide (ZnO) filled polyester composites. The Composites were prepared by using polyester as the matrix, methyl ethyl ketone peroxide (MEKPO) as the catalyst. The composites were filled by the zinc oxide at 0%; 1%; 3%; 5%; and 7% were molded by hot press with pressure variation of 50 psi, 75 psi, 100 psi, 125 psi and 150 psi. Composites have been molded, then tested for the characteristics Scanning Electron Microscope (SEM) and tests of tensile strength. The best result of tensile strength, impact and flexural were found on the addition of 3% ZnO at a pressure of 150 psi with a tensile strength of 54 MPa. SEM characterization showed a rougher surface is breaking up on the addition of 3% ZnO at a pressure of 150 psi because had a good wetting between matrix and filler ZnO.